Effects of Climate Threshold on Sorghum Production in Guinea-Savannah, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
To explore the optimal climatic conditions conducive to maximum sorghum yield and to understand the sources of variability in the study area, both cross-sectional and time series data were employed. Climate data were sourced from the Nigeria Meteorological Station (NIMET), while sorghum yield data were gathered from the Nigerian Bureau of Statistics (NBS) and state Ministry of Agriculture. Findings derived from the Just-Pope Production Model reveal that factors such as sorghum seed quantity, fertilizer quantity, the proportion of family labor engaged in farm activities, and farm size contribute to increased yield variance among sorghum farmers. Additionally, both seed and fertilizer quantities were observed to heighten sorghum farmers’ yield risk within the study area. Over the considered period, sorghum yield exhibited a positive growth rate of 2.4%. Analysis of climate variables unveiled that temperature escalation amplified the yield risk among sorghum farmers, albeit without severe consequences. Notably, there was a deceleration observed in sorghum growth. Growing Degree Days (GDD) were found to mitigate yield risk for sorghum, with an increase of one GDD unit inducing a yield uptick in the states under examination. However, as anticipated, the impact of increased extreme temperatures, as measured by Harmful Degree Days (HDD), negatively influenced sorghum yield. Long-run estimates underscored a positive correlation between temperature and sorghum yield, while rainfall exhibited a negative effect.
Keywords: Climate; Threshold; Sorghum; Guinea-savannah